The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s10195-017-0448-9
|View full text |Cite
|
Sign up to set email alerts
|

The influence of femoral tunnel length on graft rupture after anterior cruciate ligament reconstruction

Abstract: BackgroundFor ACL reconstruction, the minimum length of the femoral tunnel and the flexor tendon graft length needed within the tunnel for proper integration have not been defined. The aim of this study was to assess whether a short tunnel is a risk factor for poor prognosis and re-rupture by comparing the outcomes of patients with short femoral tunnels to those of patients with longer tunnels.Materials and methodsA retrospective observational study of 80 patients who underwent ACL reconstruction using flexor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…This theoretical risk of inadequate tunnel length bears the potential for clinical relevance, especially when deep flexion is unable to be achieved because of a patient’s body habitus, musculature, or intrinsic flexibility. While this suggests a potential technical advantage with the use of AM-FR, a previous study by Guglielmetti et al 10 did not observe a difference in rerupture rates between patients with <1.5 cm versus >2.5 cm of graft within the femoral tunnel. The theoretical risk of insufficient tunnel size has also not been investigated in clinical studies comparing AM-FR and AM-RR to determine the clinical importance of these suggested differences.…”
Section: Discussionmentioning
confidence: 72%
“…This theoretical risk of inadequate tunnel length bears the potential for clinical relevance, especially when deep flexion is unable to be achieved because of a patient’s body habitus, musculature, or intrinsic flexibility. While this suggests a potential technical advantage with the use of AM-FR, a previous study by Guglielmetti et al 10 did not observe a difference in rerupture rates between patients with <1.5 cm versus >2.5 cm of graft within the femoral tunnel. The theoretical risk of insufficient tunnel size has also not been investigated in clinical studies comparing AM-FR and AM-RR to determine the clinical importance of these suggested differences.…”
Section: Discussionmentioning
confidence: 72%
“…The changes in tunnel length among the various ASRs were about 1 mm, and the shortest tunnel length was 27.22 mm. Existing studies found that the BioMed Research International minimum required tunnel length was 25 mm for successful reconstruction surgery [35,39]. Thus, the ASR of the distal femur might not be an essential factor for determining adequate tunnel length.…”
Section: Discussionmentioning
confidence: 99%
“…For successful ACL reconstruction, many researchers have focused on the optimal tunnel position with tunnelling technique through biomechanical simulations [ 6 , 25 , 34 , 35 ]. However, anatomical characteristics of the knee were not considered in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, although many studies suggest a minimum of 20 mm of soft‐tissue graft within the tunnel, a recent study by Mariscalco et al (for the MOON cohort) showed no difference in patient‐reported outcome measures with hamstring reconstructions (using a suspensory device) in tunnels measuring 14–35 mm [25]. Further, Guglielmatti et al found no increase in graft rupture with short femoral tunnels [9]. Therefore, the benefit of such a small increase may not exist for hamstring reconstructions and is less relevant to other graft choices requiring tunnel length of only 20–25 mm.…”
Section: Discussionmentioning
confidence: 99%